Anorexigenic lipopeptides ameliorate central insulin signaling and attenuate tau phosphorylation in hippocampi of mice with monosodium glutamate-induced obesity - Špolcová, Andrea; Mikulášková, Barbora; Holubová, Martina; Nagelová, Veronika; Pirnik, Zdenko; Zemenová, Jana; Haluzík, Martin; Železná, Blanka; Galas, Marie-Christine; Maletínská, Lenka (Journal of Alzheimer's disease, 2015)
Numerous epidemiological and experimental studies have demonstrated that patients who suffer from metabolic disorders, such as type 2 diabetes mellitus (T2DM) or obesity, have higher risks of cognitive dysfunction and of Alzheimer's disease (AD). Impaired insulin signaling in the brain could contribute to the formation of neurofibrillary tangles, which contain an abnormally hyperphosphorylated tau protein. This study aimed to determine whether potential tau hyperphosphorylation could be detected in an obesity-induced pre-diabetes state and whether anorexigenic agents could affect this state. We demonstrated that 6-month-old mice with monosodium glutamate (MSG) obesity, which represent a model of obesity-induced pre-diabetes, had increased tau phosphorylation at Ser396 and Thr231 in the hippocampus compared with the controls, as determined by western blots. Two weeks of subcutaneous treatment with a lipidized analog of prolactin-releasing peptide (palm-PrRP31) or with the T2DM drug liraglutide, which both had a central anorexigenic effect, resulted in increased phosphorylation of the insulin cascade kinases PDK1 (Ser241), Akt (Thr308), and GSK-3β (Ser9). Furthermore, these drugs attenuated phosphorylation at Ser396, Thr231, and Thr212 of tau and of the primary tau kinases in the hippocampi of 6-month-old MSG-obese mice. We identified tau hyperphosphorylation in the obesity-induced pre-diabetes state in MSG-obese mice and demonstrated the beneficial effects of palm-PrRP31 and liraglutide, both of known central anorexigenic effects, on hippocampal insulin signaling and on tau phosphorylation.
Keywords: proteiny tau; Time Factors; Phosphorylation; zvířata; Male; tau Proteins; chuťové esence; signální transdukce; Insulins; hormon uvolňující prolaktin; Prolactin-Releasing Hormone; glutamát sodný; Flavoring Agents; glukózový toleranční test; Mice; Animals; mužské pohlaví; tělesná hmotnost; lipopeptidy; Body Weight; Receptors, G-Protein-Coupled; časové faktory; Analysis of Variance; Disease Models, Animal; Glucose Tolerance Test; Lipopeptides; receptory spřažené s G-proteiny; Obesity; modely nemocí na zvířatech; Hippocampus; glukagonu podobný peptid 1; fosforylace; inzuliny; Glucagon-Like Peptide 1; obezita; hipokampus; Sodium Glutamate; analýza rozptylu; myši; Signal Transduction